MONOLITh: a soft non-pneumatic foam robot with a functional mesh skin for use in delicate environments. (3rd April 2022) - Scibelli, Anthony E.; Donatelli, Cassandra M.; Tidswell, Ben K.; Payton, Micah R.; Tytell, Eric D.; Trimmer, Barry A.
Abstract : MONOLITh is a bioinspired, untethered crawling soft robot. The body is made from a lightweight reticulated foam that provides passive shape restoration and supports the internally embedded components (motors, battery, wireless controller). DC motors pull tendons attached to an external fabric that distributes forces, and novel differential friction elements enable forward locomotion. This robot is capable of traveling at a maximum speed of 0.1 body lengths/sec, lifting 100% of its body weight, while remaining 95% soft materials by volume. We expect that the design principles and materials used to make this low cost and scalable robot will lead to the development of useful, and commercially viable, terrestrial or extraterrestrial vehicles. GRAPHICAL ABSTRACT: UF0001